PSI-12 Performance and carcass measurements by rabbits offered diets with and without a phytogenic feed additive. (30th November 2020) - Wilbers, Kimberly; Shanks, Bruce C; Caldwell, James D; Koppen, Megan; Adams, Kevin
Abstract: Weaning stress and other environmental conditions can impact growing rabbit performance and carcass measurements. Therefore, investigating a feed ingredient that may mitigate these effects is important. The objective of this study was to determine if the addition of a phytogenic feed additive would improve performance and carcass measurements of growing rabbits. On October 22 nd, 2018, a total of 16 (1.01 ± 0.02 kg BW) New Zealand White male rabbits were weaned and stratified by BW and allocated randomly to 1 of 2 groups representing 2 treatments: 1) Control (C; no phytogenic; n = 8) and 2) 454 g/ton phytogenic feed additive (PHYTO; n = 8). During the 42-d study, rabbits were housed in individual cages and offered a 18% CP and 2% fat commercial grower diet. All rabbits had ad libitum access to feed and water. Rabbits were weighed at the start of the study and weekly thereafter until the end of the feeding period when they were transported to a local abattoir, harvested, and carcass measurements recorded. Data were analyzed using PROC MIXED of SAS. Start weight, weekly BW, end BW, weekly gain, total gain, weekly intake, total intake, and G:F did not differ (P ≥ 0.11) between treatments. Carcass shrink percentage was greater (P = 0.003) from PHYTO compared with C. Whereas, HCW and dressing percentage were greater (P < 0.05) from C compared with PHYTO. Loin width did not differ (P = 0.89) between treatments. Ultimate pH was lower (P = 0.02) from PHYTO compared with C. Therefore, offering this specific phytogenic to weaned rabbits may not improve performance, but may impact certain carcass measurements. Further research is warranted to explore phytogenic impacts on carcass acceptability.